Mencintai tanpa syarat: aplikasi model “unconditional positive regard” - Nanum Sofia (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2015)
Abstract: To love unconditionally: The application model of “Unconditional Positive Regard”. This research has a purpose to measure how deep the love that exist in the married couple. This research applies the “unconditional positive regard model” that made by researcher itself based on the concept by Carl R. Rogers. The subject of this research involves three married couples. The result of this research indicates that wether husband and wife are situated in UPR (unconditional positive regard) within intermediate level therefore need for treatment. To increase UPR, they therefore are given stimulus 4 together. The final result that married couple gets insight and after recheck with the same model, they UPR increase.Keyword: Model, Unconditional positive regard, Love Abstrak: Mencintai tanpa syarat: aplikasi model “unconditional positive regard”. Penelitian ini bertujuan untuk mengukur sedalam apakah cinta pada pasangan suami-istri. Penelitian ini menggunakan “model unconditional positive regard” yang dibuat sendiri oleh peneliti berdasarkan konsep Carl R. Rogers. Subjek penelitian melibatkan 3 pasang suami istri. Hasil penelitian ini mengindikasikan bahwa suami ataupun istri berada pada UPR (unconditional positive regard) tingkat sedang, sehingga memerlukan peningkatan. Untuk meningkatkan UPR, diberikan stimulus 4 dan diuji kembali dengan model yang sama, hasilnya UPR meningkat.Kata Kunci: Model, Unconditional positive regard, Cinta